POTENSI EKSTRAK KULIT BUAH JENGKOL (Pithecellobium lobatum Benth.) SEBAGAI TERMITISIDA NABATI PADA KAYU PULAI (Alstonia scholaris L.) - Affandi, Zul; Sulaeman, Rudianda; Budiani, Evi Sri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Pulai(Alstonia scholaris L.) wood widely used because it’s easy to obtained and demand is quite high. Pulai wood included in durable class V and strong class IV-V, so easily attacked by termite (wood destructive organisms). To prevent and reduce the impact of termite attack, we can utilize natural materials as basic materials botanical termiticide. Materials derived from plants are guaranteed environmentally friendly, because it’s quickly decomposes on ground and does not harm the non-target. One of the potential is jengkol (Pithecellobium lobatum Benth.) fruit skin. This research aimed to know about the effectiveness and potential of jengkol fruit skin extract as botanical termiticide to controlling termite (Coptotermes curvignathus Holmgren.) attack at pulai wood. This research used Completely Random Design method wich consists of 4 treatments and 3 replicates with concentration levels of extract, T0 = 0 g/l of water (0%); T1 = 21 g/l of water (2%); T2 = 42 g/l of water (4%); T3 = 64 g/l of water (6%). The results showed that the application jengkol fruit skin extract at the concentration 4% and 6% is the best treatment to controlling termite, with total mortality amounted to 100%. The value of retention meets National Standards ofIndonesia amounted to 8,58kg/m3 (interior) 4% treatment and 12,35 kg/m3 (exterior) 6% treatment. Both of it also, able to improve the resilience of pulai wood into class II with termite consumption levels lower than control treatment. Jengkol fruit skin extract is effective and has potential as base material botanical termiticide. Keywords: Pithecellobium lobatum Benth., Alstonia scholaris L., Coptotermes curvignathus Holmgren., Botanical Termiticide